Untreated newly diagnosed essential hypertension is associated with nonalcoholic fatty liver disease in a population of a hypertensive center - Michopoulos, S.; Chouzouri, V.I.; Manios, E.D.; Grapsa, E.; Antoniou, Z.; Papadimitriou, C.A.; Zakopoulos, N.; Dimopoulos, A.-M. (Clinical and Experimental Gastroenterology, 2016)
Purpose: Recent studies have demonstrated that hypertension (HTN) is associated with non- alcoholic fatty liver disease (NAFLD) in treated hypertensive patients. The aim of this study was to investigate the association between newly diagnosed essential HTN and NAFLD in untreated hypertensive patients. Patients and methods: A consecutive series of 240 subjects (143 hypertensives and 97 normotensives), aged 30-80 years, without diabetes mellitus were enrolled in the study. Subjects with 24-hour systolic blood pressure (SBP) values ≥130 mmHg and/or diastolic BP values ≥80 mmHg were defined as hypertensives. NAFLD was defined as the presence of liver hyperechogenicity on ultrasound. Results: Body mass index (P=0.002) and essential HTN (P=0.016) were independently associated with NAFLD in the multivariate logistic regression model. Furthermore, the multivariate analysis revealed that morning SBP (P=0.044) was independently associated with NAFLD. Conclusion: Untreated, newly diagnosed essential HTN is independently associated with NAFLD. Ambulatory BP monitoring could be used for the diagnosis of essential HTN in patients with NAFLD. © 2016 Michopoulos et al.
Keywords: ambulatory blood pressure; Body Mass Index; Hypertension; Liver steatosis; Nonalcoholic fatty liver disease